The effect conscious sedation used for an endoscopic procedure has on attention - Hassem, Tasneem (My University, 2015)
Past literature conducted on the effects of attention following conscious sedation highlight a significant decrease in attention. However, the sleep that occurs during sedation is associated with normal sleep and therefore there is a possibility that this sleep may repay sleep debt and could increase attention. As a result the following research explored the effects of conscious sedation on both the focus and encode elements of attention and the impact of propofol dosage on attention. The sample was formed by 31 outpatients from the Rosebank NetCare hospital undergoing an endoscopic procedure. Pre- and post-test measures of attention included the D-KEFS Color-Word Interference condition 1 and 2, Digit Span Forward subtest from the WAIS III as well as the Mental Control subtest from the WMS IV. Using a Matched Paired T-Test and a Wilcoxon Signed Ranked Test the following results were observed; significant results were found between the pre- and post-test scores on the D-KEFS Color Naming condition 1 number of corrected errors (z = -1.93 p=0.05), as well as on the Digit Span Forward subtest(z = -2.55 p=0.01). For the remainder of the attention measures non-significant results were produced (p>0.05).When assessing the impact of the dosage of propofol using an Independent Samples t-test and a Mann-Whitney U-test, non-significant results (p>0.05) were produced for all the focus and encode elements of attention. The following results indicates the sleep that occurs during conscious sedation does not improve attention, therefore individuals’ undergoing conscious sedation should adhere to post-sedation discharge guidelines.
A research project submitted in partial fulfilment of the requirements for the degree of MA (Research Psychology) by course work and research report in the faculty of Humanities, University of the Witwatersrand, Johannesburg, (December 2014)